2014
DOI: 10.1186/preaccept-1465471670128835
|View full text |Cite
|
Sign up to set email alerts
|

Back pain in children surveyed with weekly text messages - a 2.5 year prospective school cohort study

Abstract: Background: Back pain is reported to occur already in childhood, but its development at that age is not well understood. The aims of this study were to describe BP in children aged 6-12 years, and to investigate any sex and age differences. Methods: Data on back pain (defined as pain in the neck, mid back and/or lower back) were collected once a week from parents replying to automated text-messages over 2.5 school years from 2008 till 2011. The prevalence estimates were presented as percentages and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Therefore, back pain educational programs have been developed and evaluated for elementary school children [7,[11][12][13][14][15][16][17][18][19][20][21]. For example, Cardon et al used a school-based educational program on back care principles among Belgian pupils in which children were taught through guided discovery and active hands-on methods such as games and dramatic plays [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, back pain educational programs have been developed and evaluated for elementary school children [7,[11][12][13][14][15][16][17][18][19][20][21]. For example, Cardon et al used a school-based educational program on back care principles among Belgian pupils in which children were taught through guided discovery and active hands-on methods such as games and dramatic plays [18].…”
Section: Introductionmentioning
confidence: 99%
“…The results established by Franz et al also suggested that knowledge about back pain risk factors in childhood might lead to early prevention. They even argued that changes in actual back care-related behavior among children was very difficult [15] since such changes would be more likely to occur when there were subsequent changes in cognitive determinants of behavior [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSK pain in different regions of the body (spine, upper extremity (UE) and lower extremity (LE)) has been described in detail in children participating in the Childhood Health, Activity and Motor Performance School Study (CHAMPS Study-DK) [ 8 , 23 26 ]. LE pain and spinal pain were common and recurrent in the children, whereas UE pain was less common and most often short-lasting [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the frequency of spinal pain increase with age [ 4 , 6 , 10 , 20 ]. To obtain a satisfying frequency of spinal pain, only data from the last 2 years of the study period (from August 2012 to June 2014) was used in this study.…”
Section: Methodsmentioning
confidence: 99%